Design, deployment and functional tests of the online event filter for the ATLAS experiment at LHC - Armstrong, S.; dos Anjos, A.; Baines, J.T.M.; Bee, C.P.; Biglietti, M.; Bogaerts, J.A.; Boisvert, V.; Bosman, M.; Caron, B.; Casado, P.; Cataldi, G.; Cavalli, D.; et al. (IEEE transactions on nuclear science, 2005)
The Event Filter (EF) selection stage is a fundamental component of the ATLAS Trigger and Data Acquisition architecture. Its primary function is the reduction of data flow and rate to values acceptable by the mass storage operations and by the subsequent offline data reconstruction and analysis steps. The computing instrument of the EF is organized as a set of independent subfarms, each connected to one output of the Event Builder (EB) switch fabric. Each subfarm comprises a number of processors analyzing several complete events in parallel. This paper describes the design of the ATLAS EF system, its deployment in the 2004 ATLAS combined test beam together with some examples of integrating selection and monitoring algorithms. Since the processing algorithms are not explicitly designed for EF but are adapted from the offline ones, special emphasis is reserved to system reliability and data security, in particular for the case of failures in the processing algorithms. Other key design elements have been system modularity and scalability. The EF shall be able to follow technology evolution and should allow for using additional processing resources possibly remotely located